Angiosperm flora of sadar upazila of Munshiganj district, Bangladesh (Bangladesh Journal of Plant Taxonomy, 2013)
Investigation to make inventory of the angiosperm species diversity in the local floraof Sadar Upazila of Munshiganj district has been made. A total of 240 taxa in 186 genera under 68 families are recognized, and enumerated citing each species with updated nomenclature, Bangla names, habit, habitat, phenology, potential value, status of occurrence in the area and voucher specimens. Of these 240 taxa, Magnoliopsida is represented by 195 taxa in 146 genera and 55 families, whereas Liliopsida by 45 taxa under 40 genera and 13 families. The local people of the area use over 50 medicinal plants as sources of medicine for their primary health care. Some species are assessed as rare to this local flora which need to be brought under conservation management for environmental sustainability of the area.DOI: http://dx.doi.org/10.3329/bjpt.v20i2.17396Bangladesh J. Plant Taxon. 20(2): 213-231, 2013